Ways to Ensure the Competitiveness of an Enterprise (on the Example of the Enterprise “Great Wall Automobile”) - He, Zilong (Kharkiv : V. N. Karazin Kharkiv National University, 2024)
The master’s thesis explores theoretical and practical aspects of ensuring enterprise competitiveness based on the case of Great Wall Automobile. The study analyzes the external environment, internal performance, and financial indicators of the company, identifying key development challenges such as a limited product structure, an imperfect financial system, and difficulties in transitioning to new energy technologies. The enterprise value is assessed, and recommendations are proposed to enhance competitiveness, including product structure optimization, improved financial management, and strengthening of innovation capacity.

У магістерській роботі досліджено теоретичні та практичні аспекти забезпечення конкурентоспроможності підприємства на прикладі Great Wall Automobile. Проаналізовано зовнішнє середовище, внутрішній стан і фінансові показники компанії, виявлено основні проблеми розвитку, зокрема обмежену продуктову структуру, недосконалість фінансової системи та виклики переходу до нових енергетичних технологій. Оцінено вартість підприємства та запропоновано рекомендації щодо підвищення його конкурентоспроможності, включаючи оптимізацію структури продукції, покращення управління фінансами та розвиток інноваційного потенціалу.
Шляхи забезпечення конкурентоспроможності підприємства (на прикладі «Great Wall Automobile»)
Керівник роботи : Юлія Олександрівна Лазебник, доктор економічних наук, доцент, професор кафедри управління та адміністрування, Навчально-науковий інститут "Каразінська школа бізнесу"
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; competitiveness; конкурентоспроможність; автомобільне виробництво; automobile production; виробник в Китаї; manufacturer in China; management; менеджмент